The prospective statute of limitations as lack of interest in criminal action (Revista do Tribunal Regional Federal da 3ª Região, 2013)
The object of this study is the analysis of prescription (extinctive cause of punishability) in its perspective modality, a theory that has long been totally repugnant to doctrine and jurisprudence and which is gaining strength, being defended even by accusatory bodies. Although the statute of limitations in criminal law is an extinctive cause of punishability, an institute related to substantive law, in this work we will seek to understand it by studying its intrinsic elements of substantive law, but applied as grounds for rejecting the complaint for lack of just cause to bring the action.
Keywords: criminal action; prescription in perspective; cause extinguishing punishability; rejection of complaint